Rapid implementation of telemedicine and home oxygen treatment for COVID-19 patients at the verge of the Omicron wave in Turku, Finland - Hänninen, Janne (My University, 2023)
The COVID-19 pandemic has burdened healthcare systems worldwide, especially after the emergence of the Omicron variant. As one of the first centres in Finland, an app-based home monitoring protocol combined with portable home oxygen treatment was piloted in Turku. The objectives for the study were to describe and evaluate the safety, clinical outcomes and usefulness of the home treatment as well as evaluate the cost-benefit aspects. This is an observational cohort study consisting of hospitalized patients due to COVID-19. The data was analysed retrospectively. A total of 19 COVID-19 patients were included in the study from 3 different hospital wards in the Turku city region, South-West Finland during the study period between 1st of January 2022 and 30th of September 2022. All patients were male. The median duration of home oxygen treatment was 13 days, and the median duration of home monitoring was 18 days. A total of 210,5 hospital days were prevented and thus a total sum of €144,490 of healthcare expenditure (on average 9 days and €7,605 per patient) was saved. During the follow-up, no major safety issues, complications, or discomfort towards the treatment were reported. Home monitoring combined with portable oxygen treatment seems to be a safe, patient friendly and economically beneficial way to treat COVID-19 patients who are recovering from severe SARS-CoV-2 infection. This form of treatment could also potentially be utilized in other pulmonary infections in otherwise stable patients who still need treatment and monitoring.
Keywords: COVID-19, SARS-CoV-2, telemedicine, oxygen